Preparation process of building backing plate and product
By placing fiber mesh cloth on both sides of the extruded board and coating interface treatment agent and mortar emulsion, the problem of easy separation of the extruded backing board in a humid environment is solved, and the waterproof, moisture-proof, thermal insulation, sound insulation and flame retardant properties of the backing board are improved.
Patent Information
- Application Number
- CN202510135616.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-22
AI Technical Summary
When applied to environments that require long-term waterproofing and moisture-proof, extruded backing plates are prone to absorb moisture, resulting in separation between mortar materials, grid fabrics and extruded plates, reducing application performance.
A fiber mesh cloth is placed on both sides of the extruded board and the interface treatment agent is coated. After the interface treatment agent is set, the mortar emulsion is applied and dried to prepare a building backing board.
The interface treatment agent enhances the bonding force between the fiber mesh cloth and the extruded board, forms a waterproof film, improves the bonding stability of the mortar emulsion to the extruded board and the fiber mesh cloth, and improves the waterproof, moisture-proof, thermal insulation, sound insulation and flame retardant properties of the backing board, and is suitable for humid environments.
Smart Images

Figure BDA0005263109440000051 
Figure BDA0005263109440000061 
Figure BDA0005263109440000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of functional building materials, and more specifically, to a preparation process and product of a building backing board. Background Art
[0002] Building backing board is a material commonly used in building decoration, which mainly plays the role of supporting, protecting and strengthening the wall structure. Building backing board is usually made of materials such as plastic, metal or wood, and is placed on the back of the material to be protected to improve its durability and impact resistance. Backing board has a wide range of applications in the construction field. For example, it can be used in glass curtain wall systems, bathrooms, basements, exterior walls, swimming pools, terraces, roofs and other scenes. It has waterproof, moisture-proof, heat-insulating, sound-proof and other functions.
[0003] Taking extruded backing board as an example, the extruded backing board is generally composed of mesh cloth covered on both sides of the extruded board, and the mesh cloth is bonded and fixed to the surface of the extruded board with mortar material. This extruded backing board has good compressive strength and supporting performance, but when used in environments such as bathrooms that require long-term waterproofing and moisture-proofing, it is easy to absorb moisture in the bathroom, causing separation between the mortar material, mesh cloth and extruded board, reducing the application performance of the extruded backing board. Summary of the invention
[0004] In order to solve the problem that when extruded backing boards are used in environments such as bathrooms that require long-term waterproofing and moisture-proofing, they easily absorb moisture in the bathroom, causing separation between the mortar material, mesh cloth and the extruded board, thereby reducing the application performance of the extruded backing boards, the present application provides a preparation process and product of a building backing board.
[0005] In the first aspect, the present application provides a preparation process of a building backing board, which adopts the following technical solution: A preparation process of a building backing board comprises the following steps: S1, cutting the extruded board and smoothing the surface; S2, placing a fiber mesh cloth on one surface of the extruded board and coating the fiber mesh cloth with an interface treatment agent to set the shape; S3, coating the mortar emulsion on the surface of the fiber mesh cloth and drying; S4, turn over, place fiber mesh cloth on the other surface of the extruded board, and apply interface treatment agent on the fiber mesh cloth to fix the shape; apply mortar emulsion on the surface of the fiber mesh cloth, dry and maintain, and obtain the building backing board.
[0006] By adopting the above technical scheme, firstly, using the extruded board as the core material, the dimensional accuracy and flatness of the extruded board are ensured by cutting and surface smoothing the extruded board, and the quality of subsequent processing is improved. After that, a fiber mesh cloth is placed on one side of the extruded board and coated with an interface treatment agent and then shaped. The interface treatment agent is in a semi-dry state by shaping. The interface treatment agent enhances the bonding force between the fiber mesh cloth and the extruded board, and can form a waterproof film on the extruded board and the fiber mesh cloth at the same time, which plays a role in preventing water penetration and improving the bonding stability of the subsequent mortar emulsion with the extruded board and the fiber mesh cloth. After that, the mortar emulsion is coated on the surface of the fiber mesh cloth and dried, so that the mortar emulsion can be stably bonded with the fiber mesh cloth and the extruded board under the action of the interface treatment agent, and the overall strength and durability of the backing board are improved. After that, the same steps are repeated on the other side of the extruded board, and finally, after maintenance, the building backing board of the present application is obtained. The building backing board produced by the preparation process of the present application has good waterproof and moisture-proof properties, thermal insulation, sound insulation and flame retardancy, can maintain excellent stability during long-term use, and the building backing board is not prone to separation and cracking problems, and is particularly suitable for humid environments such as bathrooms and kitchens.
[0007] Preferably, the fiber mesh cloth in step S2 is any one of glass fiber mesh cloth, carbon fiber mesh cloth and polypropylene mesh cloth.
[0008] By adopting the above technical solution, the fiber mesh cloth has good mechanical properties such as tensile strength and tear resistance, and can significantly improve the mechanical strength and durability of the building backing board.
[0009] Preferably, the interface treatment agent in step S2 is prepared from the following raw materials in parts by weight: 25-35 parts of water-based polyurethane emulsion 18-25 parts of hydroxyl-terminated polybutadiene 5-10 parts of dimethylol propionic acid 3-5 parts of long chain alkyl glycidyl ether 2-4 parts hydrophobically modified hydroxyethyl cellulose 1-3 parts of curing agent 20-30 parts of water.
[0010] By adopting the above technical scheme, the surface treatment agent of the present application uses water-based polyurethane emulsion and terminal hydroxyl polybutadiene as a matrix to improve the flexibility and bonding performance of the interface treatment agent, uses dihydroxymethylpropionic acid as a chain extender, long-chain alkyl glycidyl ether as a bonding aid, and hydrophobically modified hydroxyethyl cellulose as a thickener. Under the action of a curing agent, a cross-linking reaction is carried out, which can significantly improve the bonding force between the fiber mesh cloth and the extruded board, effectively prevent the separation phenomenon caused by moisture infiltration, thereby improving the overall stability and durability of the building backing board.
[0011] Preferably, the long-chain alkyl glycidyl ether is dodecyl glycidyl ether and / or tetradecyl glycidyl ether.
[0012] By adopting the above technical scheme, the long-chain alkyl glycidyl ether has a hydrophobic long-chain alkyl group, which can provide better bonding and hydrophobic properties for the interface treatment agent while being interwoven and dispersed with the polyurethane system, and can significantly improve the flexibility, water resistance and bonding properties of the interface treatment agent, thereby effectively preventing the separation and cracking between the mortar emulsion, fiber mesh cloth and extruded board, and enhancing the overall stability of the building backing board.
[0013] Preferably, the coating amount of the interface treatment agent in step S2 is 50-70 g / m 2 The setting temperature of the interface treatment agent is 70-90℃, and the setting time is 3-6min.
[0014] By adopting the above technical solution, the optimal coating amount of the interface treatment agent is controlled to ensure sufficient coating thickness, improve the bonding force between the fiber mesh cloth and the extruded board, and reduce the separation phenomenon caused by water penetration. The optimal setting time and setting temperature can make the interface treatment agent not completely solidified while obtaining initial solidification, and can shape the fiber mesh cloth while improving the subsequent adhesion stability with the mortar emulsion, thereby improving the bonding force between the interface treatment agent and the fiber mesh cloth and the extruded board, and improving the stability and durability of the overall building backing board structure.
[0015] Preferably, the mortar emulsion is prepared by mixing a polymer binder and water in a weight ratio of (0.25-0.3):1.
[0016] Preferably, the polymer binder is prepared from the following raw materials in parts by weight: 20-40 parts of cement 30-50 parts of quartz sand Styrene acrylic emulsion 25-35 parts Flame retardant 20-30 parts Heat insulation agent 10-20 parts 4-8 parts of adhesive additive 2-3 parts of silicone hydrophobic agent Defoamer 0.2-0.4 parts Preservative 0.1-0.2 parts.
[0017] By adopting the above technical solution, the polymer binder and water in a better ratio are mixed, and the obtained mortar emulsion has good fluidity and coating performance, and can significantly improve its bonding performance and stability. The polymer binder uses cement and quartz sand in better amounts as the basic material body, styrene acrylic emulsion and bonding aid as the adhesion system of cement and quartz sand, and is compounded with heat insulating agent, flame retardant, silicone hydrophobic agent, defoaming agent and preservative. The polymer binder obtained in this way has good waterproofness, flame retardancy, heat insulation and adhesion stability, and can stably adhere to the surface of extruded board and fiber mesh cloth under the synergistic effect of interface treatment agent, significantly improving the overall performance of building backing board.
[0018] Preferably, the bonding aid is composed of hydrophobically modified hydroxyethyl cellulose and magnesium aluminum silicate in a weight ratio of (2-3):1.
[0019] By adopting the above technical scheme, the hydrophobically modified hydroxyethyl cellulose and magnesium aluminum silicate in an optimal weight ratio produce a better synergistic effect, which can improve the adhesion stability and waterproofness of the prepared polymer binder and prevent the interface separation problem caused by water penetration.
[0020] Preferably, the coating amount of the mortar emulsion is 1-1.2 kg / m 2 , drying temperature is 45-55℃, drying time is 2-4h; curing time is 7-10 days.
[0021] By adopting the above technical solution, the mortar emulsion is applied to the surface of the fiber mesh cloth with an optimal coating amount, and a surface layer with good compressive strength is formed on the surface of the fiber mesh cloth. The optimal drying time and temperature can make the mortar emulsion dry stably, improve the adhesion stability and reduce the deformation and cracking problems. If the drying temperature is too high, local stress unevenness will occur, causing the mortar emulsion to crack. The optimal curing time can make the layers fully bonded and fixed, further improving the overall performance and service life of the building backing board.
[0022] In a second aspect, the present application provides a building backing board, which adopts the following technical solution: A building backing board is prepared by the above preparation process.
[0023] By adopting the above technical solution, the building backing board of the present application has good compressive resistance, thermal insulation, sound insulation, waterproof and moisture-proof performance with extruded board as the core material. The fiber mesh cloth is laminated with an interface treatment agent, and then the mortar emulsion is coated on the outer surface of the fiber mesh cloth and dried. The prepared building backing board has good waterproof and moisture-proof properties, thermal insulation, sound insulation, flame retardancy and compressive resistance, and is suitable for environments prone to moisture, such as bathrooms, kitchens, basements, etc.
[0024] In summary, the present application includes at least one of the following beneficial technical effects: 1. The preparation process of the building backing board of the present application is to place fiber mesh cloth on both sides of the extruded board and apply an interface treatment agent, and then apply a mortar emulsion and dry it after the interface treatment agent is fixed. The building backing board prepared by the preparation process of the present application has good waterproof and moisture-proof properties, thermal insulation, sound insulation and flame retardancy, and can maintain excellent stability during long-term use. The building backing board is not prone to separation and cracking, and is particularly suitable for humid environments such as bathrooms and kitchens.
[0025] 2. The interface treatment agent is prepared by using water-based polyurethane emulsion, terminal hydroxy polybutadiene, dimethylol propionic acid, long-chain alkyl glycidyl ether, hydrophobically modified hydroxyethyl cellulose, curing agent and water to enhance the bonding force between the fiber mesh cloth and the extruded board. At the same time, a waterproof film can be formed on the extruded board and the fiber mesh cloth to prevent water penetration and improve the bonding stability of the subsequent mortar emulsion with the extruded board and the fiber mesh cloth.
[0026] 3. The polymer binder of the present application is compounded with water to form a mortar emulsion, which is then applied to the surface of the fiber mesh cloth to further give the building backing board good waterproof and moisture-proof, thermal insulation, sound insulation and flame retardant properties to meet the needs of different application scenarios. DETAILED DESCRIPTION
[0027] The present application is further described in detail below in conjunction with embodiments.
[0028] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used: 1. Extruded board: XPS extruded board, thickness 50mm, compression strength 400KPa, thermal conductivity 0.030W / (m·K), combustion grade B1; 2. Glass fiber mesh cloth: thickness 2mm, mesh 8*8mm, weight 100g / m 2 ; 3. Water-based polyurethane emulsion: Anda Huatai, model AH-1730; 4. Hydroxyl-terminated polybutadiene: Lana White, molecular weight 3000-4500; 5. Hydrophobically modified hydroxyethyl cellulose: Natrosol TM HMHEC; 6. Curing agent: Zengmao Chemical, ZS-2603; 7. Cement: Washi cement, M32.5; 8. Quartz sand: 325 mesh; 9. Styrene acrylic emulsion: Dow Primer DC-420 styrene acrylic emulsion, solid content 48%; 10. Silicone hydrophobic agent: Wacker BS206; 11. Defoaming agent: Shengbang silicone SI-X101; 12. Preservative: Methylisothiazolinone MIT-50; 13. Heat insulation agent: hollow glass microspheres, Zhengzhou Shenglait, model HS60, average particle size 16μm; 14. Flame retardant: aluminum hydroxide: 325 mesh; magnesium hydroxide: 325 mesh; 15. Magnesium aluminum silicate: Huaxiang Kejie, 325 mesh, specific gravity 2-2.2g / ml.
[0029] Preparation example of interface treatment agent Preparation Example 1 Preparation Example 1 discloses an interface treatment agent, which is prepared by the following steps: 0.2 kg of hydrophobically modified hydroxyethyl cellulose is added to 2 kg of water, and after dissolution, 2.5 kg of aqueous polyurethane emulsion, 1.8 kg of terminal hydroxyl polybutadiene, 0.5 kg of dihydroxymethylpropionic acid, 0.3 kg of dodecyl glycidyl ether as a long-chain alkyl glycidyl ether and 0.1 kg of a curing agent are added and stirred evenly to prepare an interface treatment agent.
[0030] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amounts of raw materials used are different, see Table 1 below for details.
[0031] Table 1 Raw material dosage table of preparation examples 1-3 Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that 1.8 kg of terminal hydroxyl polydibutylene is replaced by 1 kg of aqueous polyurethane emulsion and 0.8 kg of dihydroxymethylpropionic acid, and the rest is the same as Preparation Example 1.
[0032] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that an equal amount of dodecyl glycidyl ether is replaced by γ-glycidyloxypropyltrimethoxysilane, and the rest is the same as Preparation Example 1.
[0033] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 1 is that an equal amount of hydrophobically modified hydroxyethyl cellulose is replaced by hydroxyethyl cellulose, and the rest is the same as Preparation Example 1.
[0034] Preparation Example of Polymer Binder Preparation Example 7 Preparation Example 7 discloses a polymer binder prepared by the following steps: 2kg of cement, 3kg of quartz sand, 2kg of flame retardant (composed of magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:1), 1kg of hollow glass microspheres as a heat insulating agent, 0.4kg of bonding agent (composed of xanthan gum and cellulose ether in a weight ratio of 2:1), 0.2kg of silicone hydrophobic agent, 0.02kg of defoaming agent and 0.01kg of preservative were added into a mixer and mixed evenly to obtain a mixture; 2.5kg of styrene-acrylic emulsion was sprayed into the mixture and dispersed evenly to obtain a polymer binder.
[0035] Preparation Example 8-9 The difference between Preparation Example 8-9 and Preparation Example 7 is that the amounts of raw materials used are different, see Table 2 below for details.
[0036] Table 2 Parameters of polymer binders of Preparation Examples 7-9 Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 7 is that the viscosity aid consists of hydrophobically modified hydroxyethyl cellulose and magnesium aluminum silicate in a weight ratio of 2:1, and the rest is the same as Preparation Example 7.
[0037] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 7 is that the viscosity aid consists of hydrophobically modified hydroxyethyl cellulose and magnesium aluminum silicate in a weight ratio of 3:1, and the rest is the same as Preparation Example 7. Example
[0038] Example 1 Example 1 discloses a preparation process of a building backing board, comprising the following preparation steps: S1. Cut the extruded board and use a grinder to grind the surface to a surface flatness of 0.5 mm / m; S2, place a glass fiber mesh cloth on one surface of the polished extruded board and 2 A commercially available interface treatment agent was applied at a coating amount and set at a temperature of 70°C for 6 minutes; S3, on the surface of the fiber mesh cloth at 1.2kg / m 2 The mortar emulsion is applied with a coating amount of 2.5 kg of commercially available polymer binder and 10 kg of water, and dried at a temperature of 45°C for 4 hours; S4, turning over, continuing to operate according to the parameters in step S2 and step S3, placing a fiber mesh cloth on the other surface of the extruded board, and coating the fiber mesh cloth with an interface treatment agent to shape it; coating the surface of the fiber mesh cloth with a mortar emulsion, drying it, and curing it for 7 days to obtain a building backing board; The interface treatment agent in Example 1 is a Black Panther waterproof building materials brand, a one-component water-based polyurethane waterproof coating, model 911; the polymer binder is an Ankegu brand, a cement-based polymer bonding mortar with a bonding strength of 1.5 MPa.
[0039] Embodiment 2-5 The difference between Examples 2-5 and Example 1 is that the amounts of raw materials used and the preparation parameters are different, see Table 3 below for details.
[0040] Table 3 Raw materials and process parameters of Examples 1-5 Example 6 The difference between Example 6 and Example 3 is that the polymer binder in Example 6 is derived from Preparation Example 10, and the rest is the same as Example 3.
[0041] Example 7 The difference between Example 7 and Example 3 is that the polymer binder in Example 7 is derived from Preparation Example 11, and the rest is the same as Example 3.
[0042] Example 8 The difference between Example 8 and Example 3 is that the interface treatment agent in Example 8 is derived from Preparation Example 4, and the rest is the same as Example 3.
[0043] Example 9 The difference between Example 9 and Example 3 is that the interface treatment agent in Example 9 is derived from Preparation Example 5, and the rest is the same as Example 3.
[0044] Example 10 The difference between Example 10 and Example 3 is that the interface treatment agent in Example 10 is derived from Preparation Example 6, and the rest is the same as Example 3.
[0045] Embodiment 11 The difference between Example 11 and Example 3 is that the setting time of the interface treatment agent is 12 minutes, and the rest is the same as Example 3.
[0046] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no interface treatment agent is added, and the glass fiber mesh cloth is directly adhered to the surface of the extruded board using mortar emulsion. Other process parameters and dosages are the same as those in Example 1.
[0047] Performance testing The following is a performance test of the building backing boards prepared in Examples 1-11 and Comparative Example 1: 1. Initial tensile bond strength test According to the test method in GB / T 30595-2014 Extruded Polystyrene Board (XPS) Thin Plaster External Wall Insulation System Material 6.6.1, test the initial tensile bond strength (unit: MPa) of the cured mortar emulsion of the building backing board, test and record the test results; 2. Water-resistant tensile bond strength test According to the test method in 6.6.1 of GB / T 30595-2014 Extruded Polystyrene Board (XPS) Thin Plaster External Wall Insulation System Materials, immerse in water for 48 hours, cure for 2 hours, test the initial tensile bond strength (unit: MPa) of the cured mortar emulsion of the building backing board, test and record the test results; 3. Separation or cracking test: The building backing board that has been immersed in water for 48 hours and oxidized for 2 hours is placed in an environment with a temperature of 25°C and a humidity of 75% for 7 days to observe whether separation or cracking occurs, and the test results are recorded.
[0048] The following are the performance test data of the building backing boards prepared in Examples 1-11 and Comparative Example 1, see Table 4 below for details.
[0049] Table 4 Performance data of the building backing board of Examples 1-11 and Comparative Example 1 In combination with Examples 1-5 and Comparative Example 1, it can be seen that the building backing board obtained by shaping the glass fiber mesh cloth using the interface treatment agent of the present application and then coating the mortar emulsion and drying has good waterproof performance and is not prone to separation or cracking; in Comparative Example 1, no interface treatment agent was used, and the initial tensile bonding strength of the obtained building backing board decreased slightly, and the tensile bonding strength after water immersion treatment was only 0.1 MPa, and after the moisture test, obvious cracking and separation occurred; while in Example 3, the interface treatment agent of the present application was used, and the tensile bonding strength of the obtained building backing board was significantly improved compared with Examples 1 and 2, and the tensile bonding strength was also high after the water immersion test, and there was no problem of separation and cracking.
[0050] In combination with Examples 3-5 and Examples 6-7, by optimizing the components and proportions of the bonding aid in the mortar emulsion, the compatibility with the interface treatment agent can be further improved, thereby improving the waterproof and moisture-proof properties of the prepared building backing board.
[0051] Combining Examples 3-5 and Examples 8-10, it can be concluded that by optimizing the components of the interface treatment agent, the waterproof and moisture-proof properties of the prepared building backing board can be significantly improved. Compared with Examples 8-10, the change rate of the tensile bonding strength in Example 3 is significantly reduced, and no separation or cracking occurs.
[0052] Furthermore, it can be concluded from Example 3 and Example 11 that the waterproof and moisture-proof performance of the prepared building backing board can be significantly improved by optimizing the setting time of the interface treatment agent. Compared with Example 3, the initial tensile bonding strength and the water-resistant tensile bonding strength of Example 11 are significantly reduced, and slight separation and cracking occur. This may be because the fully cured interface treatment agent reduces the bonding performance between the mortar emulsions. Despite the presence of the interface treatment agent, it still affects the bonding strength of the mortar emulsion and reduces the stability of the building backing board.
[0053] 5. Thermal conductivity and flame retardant grade test: Referring to the test method in GB 8624, the flame retardant grade of the building backing board prepared in Example 3 was tested; referring to the test method in GB / T10801.2-2018 Extruded polystyrene foam (XPS) for thermal insulation, the thermal conductivity (unit: W / (m·K)) of the building backing board prepared in Example 3 was tested; the test results were tested and recorded, see Table 5 for details.
[0054] Table 5 Thermal conductivity and flame retardant grade of the building backing board prepared in Example 1 It can be concluded from Table 5 above that the building backing board of the present application has good flame retardancy and thermal insulation, the thermal conductivity can reach 0.026W / (m·K), and the flame retardancy grade reaches B1 grade.
[0055] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A process for preparing a building backing board, characterized in that: The following steps are involved: S1, cutting the extruded board and smoothing the surface; S2, placing a fiber mesh cloth on one surface of the extruded board and coating the fiber mesh cloth with an interface treatment agent to set the shape; S3, applying mortar emulsion on the surface of the fiber mesh cloth and drying; S4, turn over, place fiber mesh cloth on the other surface of the extruded board, and apply interface treatment agent on the fiber mesh cloth to fix the shape; apply mortar emulsion on the surface of the fiber mesh cloth, dry and maintain, and obtain the building backing board.
2. The process for preparing a building backing board according to claim 1, characterized in that: The fiber mesh cloth in step S2 is any one of glass fiber mesh cloth, carbon fiber mesh cloth and polypropylene mesh cloth.
3. The preparation process of a building backing board according to claim 1, characterized in that: The interface treatment agent in step S2 is prepared from the following raw materials in parts by weight: 25-35 parts of water-based polyurethane emulsion 18-25 parts of hydroxyl-terminated polybutadiene 5-10 parts of dimethylol propionic acid 3-5 parts of long chain alkyl glycidyl ether 2-4 parts hydrophobically modified hydroxyethyl cellulose 1-3 parts of curing agent 20-30 parts of water.
4. The preparation process of a building backing board according to claim 3, characterized in that: The long-chain alkyl glycidyl ether is dodecyl glycidyl ether and / or tetradecyl glycidyl ether.
5. The preparation process of a building backing board according to claim 1, characterized in that: The coating amount of the interface treatment agent in step S2 is 50-70 g / m 2 The setting temperature of the interface treatment agent is 70-90℃, and the setting time is 3-6min.
6. The preparation process of a building backing board according to claim 1, characterized in that: The mortar emulsion is prepared by mixing a polymer binder and water in a weight ratio of (0.25-0.3):
1.
7. The process for preparing a building backing board according to claim 6, characterized in that: The polymer binder is prepared from the following raw materials in parts by weight: 20-40 parts of cement 30-50 parts of quartz sand Styrene acrylic emulsion 25-35 parts Flame retardant 20-30 parts Heat insulation agent 10-20 parts 4-8 parts of adhesive additive 2-3 parts of silicone hydrophobic agent Defoamer 0.2-0.4 parts Preservative 0.1-0.2 parts.
8. The process for preparing a building backing board according to claim 7, characterized in that: The bonding aid is composed of hydrophobically modified hydroxyethyl cellulose and magnesium aluminum silicate in a weight ratio of (2-3):
1.
9. The process for preparing a building backing board according to claim 1, characterized in that: The coating amount of the mortar emulsion is 1-1.2 kg / m 2 , drying temperature is 45-55℃, drying time is 2-4h; curing time is 7-10 days.
10. A building backing board, characterized in that: The invention is prepared by a preparation process according to any one of claims 1 to 9.
Citation Information
Cited By
Back lining plate production equipment and manufacturing method thereof
CN121066315A
Composite mortar, preparation method of composite mortar and backing plate
CN121591447A
Composite mortar, method for producing a composite mortar and backing plate
CN121591447B
A backing plate production apparatus
CN224663952U